Pengelolaan Life Skill Dalam Pengembangan Motivasi Belajar Siswa Melalui Bimbingan Konseling SMK Siliwangi Mandiri Bogor - Ariadi; Wahyu Ningsih; Muhammad Miftahudin; Deden Hidayatul Miftahudin (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research aims to find out how life skills are managed in an effort to develop student learning motivation. Through the observation method, this research concludes that the management of life skills carried out in the context of developing students' learning motivation is an effort to develop the talents possessed by students, the aim is to build students' learning motivation, not only that, the other aim is to hone students' abilities to preparation for the future when the student has graduated from school and immediately wants to work or open a business. Managing life skills requires special attention so that it can support students' academic achievement which requires cooperation between teachers and parents in managing students' life skills. Managing students' life skills in learning activities can help students' academic side which includes cognitive, affective and psychomotor. Life skills management is also a form of positive development for students. The life skills that students themselves are very interested in are sewing, make-up, skills and cooking